Gestão ambiental integrada à construção civil : a salubridade dos trabalhadores nas empresas - Sousa, Ivo Arcaro de (2019)
The globalization process requires companies to innovate in their systems and products, continually updating their work methods by reconciling traditional practices with the implementation of new methodologies and tools, as well as combining their activities with environmental and social interests. With this perspective, this dissertation addresses issues related to the environmental management of construction companies and the salubrity of workers aiming to evaluate the conditions offered by the civil construction sector by providing a salubrious environment for workers in the stage of painting of the building and the practices management. In order to do so, five companies in the construction industry were analyzed in which questionnaires were applied to workers and managers of the companies, as well as the completion of observation files that captured information through visits of the researcher to the construction sites, as well as photographic records which verifies the veracity of the information provided. A brief characterization of the civil construction sector was necessary with respect to its legal evolution and current organizational structure and internal policy, highlighting factors that may potentiate adverse situations in this sector of the economy in order to influence the salubrious aspects of the construction sites. By this way, the growing interest in the awareness of the implementation of the environmental management system that responds to this theme by the construction companies is presented, introducing notions related to this problem, mentioning the benefits implicit in its adoption. Through the application of the instruments of this research in the construction sites can verify the inexistence of the practice of the use of PPE in the development of painting activities due to the lack of organization in the work places and storage of materials; lack of signaling that spells out information needed by internal and external users; lack of knowledge of legal documents by workers; lack of supervision by managers and responsible bodies that could identify adverse situations; lack of a management system that contemplates the residues of the construction and its disposition in the environment. In this sense, the analyzed companies, even those that have met some requirements of the active norms, have failures in the constructive system of operational or managerial character, that can be avoided, or future improved, through the planning of activities and the flow of materials and equipment, disposition and clarity in the instructions of the construction processes, besides the exercise of the inspection by the responsible organs and the managers, aiming at an improvement in the environmental quality of the labor spaces and the salubrity of the workers.